2019
DOI: 10.3389/fimmu.2019.00983
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Suppresses Breast Cancer Growth by Recruiting Immune Effector Cells Into the Tumor Microenvironment

Abstract: Infiltration of immune cells into the tumor microenvironment (TME) can regulate growth and survival of neoplastic cells, impacting tumorigenesis and tumor progression. Correlations between the number of effector immune cells present in a tumor and clinical outcomes in many human tumors, including breast, have been widely described. Current immunotherapies utilizing checkpoint inhibitors or co-stimulatory molecule agonists aim to activate effector immune cells. However, tumors often lack adequate effector cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
4
51
0
Order By: Relevance
“…Pro-inflammatory cytokines, including TNF, INF, IL-6, IL-1, and OSM, are essential mediators of adaptive and innate immune responses (28,29). Elevated serum levels of these cytokines are linked to psoriasis (30), rheumatoid arthritis (31), cancer (32), and obesity (33), pathological conditions with postulated chemerin involvement (6,26,34,35). Therefore, elucidating the underlying mechanisms involved in the regulation of chemerin expression is of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, including TNF, INF, IL-6, IL-1, and OSM, are essential mediators of adaptive and innate immune responses (28,29). Elevated serum levels of these cytokines are linked to psoriasis (30), rheumatoid arthritis (31), cancer (32), and obesity (33), pathological conditions with postulated chemerin involvement (6,26,34,35). Therefore, elucidating the underlying mechanisms involved in the regulation of chemerin expression is of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicts concerning its role in BC. A study by Pachynski et al, 2019, suggests that it inhibits BC by recruiting immune effector cells in the tumor microenvironment [123]. On the contrary, a study by El-Sagheer (2018) shows a correlation of high chemerin expression with the poor survival outcome of BC patients [124].…”
Section: Resistinmentioning
confidence: 99%
“…6A). While chemerin can recruit immune effector cells into the TME (10,46), the immunodeficiencies in NSG mice (absent NK/T/B and defective macrophage and DCs) suggested the differences in tumor growth seen could be due, in part, to tumorintrinsic factors. We analyzed ex vivo tumors and found that chemerinexpressing tumors had significantly higher PTEN and significantly lower PD-L1 levels compared with controls (Fig.…”
Section: Expression Of Chemerin In the Tme Leads To Decreased In Vivomentioning
confidence: 99%